Thermo-economic evaluation of an innovative direct steam generation solar power system using screw expanders in a tandem configuration. (5th February 2019) - Li, Pengcheng; Li, Jing; Tan, Ronghui; Wang, Yandong; Pei, Gang; Jiang, Bin; Tang, Jingchun
Highlights: Tandem screw expander-driven direct steam generation solar power system is unique. It has a relatively simple structure and good off-design behaviour. Thermodynamic and economic investigation on the tandem system is conducted. A levelized electricity cost of 0.118 /kWh is estimated. Abstract: Tandem screw expander (SE) technology is a promising solution for large volume ratio situations. Tandem SE driven direct steam generation (DSG) system is first proposed for distributed solar thermal power generation. Steam accumulator is adopted for storage due to its moderate heat source temperature. Compared with the cascade steam-organic Rankine cycle (SORC) system, the novel tandem system has simpler structure, easier control strategy and lower technical requirements, less operating and maintenance fees, more stable power output and higher security. Thermodynamic analysis and economic evaluation of the novel system are conducted based on some parameters of a recently constructed tandem SE project. Steam Rankine cycle (SRC) efficiency of 18.49% is achieved by employing built-in volume ratio ( r v, b ) of 3 for the high-pressure SE (SE1) and r v, b of 7 for the low-pressure SE (SE2). The cost-effectiveness of the system is improved as the power capacity and heat storage time increase. Levelized electricity cost (LEC) of 0.118 /kWh and payback period (PP) of 10.48 years are obtained for 1 MW tandem plant with 6.5 h heat storage. The cost of parabolic trough collectors accounts for nearly half of the total investment while the accumulators occupy less than 7%. The cost of SE2 is approximately seven times that of SE1 due to the larger design outlet volume flow rate and rotor diameter.